Transformação digital no sistema bancário: o impacto dos bancos digitais no mercado financeiro no Brasil - Santos, Paloma dos (2023)
The present study aims to analyze the impact of digital banks on the Brazilian financial system, focusing on the significant changes that have occurred in recent years and the challenges associated with this transformation. To achieve this purpose, the research adopted a quantitative approach, aiming to measure and analyze the phenomena related to the study. To collect quantitative data, a questionnaire with closed questions was used. The study investigated two main variables: customer satisfaction in relation to the services offered by digital banks and the perception of security when using these services. The results revealed that customers' perceptions of the security of digital banks, with the majority of customers feeling relatively comfortable providing personal information, although with some degree of distrust. The lack of digital security training when using digital banking services has been identified as an area requiring improvement in terms of customer education. However, customers demonstrated a positive perception of the security of digital banks and confidence in the security measures implemented. This study provides a comprehensive view of the impacts of digital banks on the Brazilian banking system.